Application of Audio Media based on The Ragam Gaya Song in Learning IPAS of Fourth Grade at SD Negeri 2 Kalanglundo - Izzah, Fairuz Nurul; Sukartono, S (Proceeding ISETH (International Summit on Science, Technology, and Humanity), 2023)
Purpose: (1) Describe the planning of the application of song-based audio media "Ragam Gaya" in IPAS learning, (2) describe the application of song-based audio media "Ragam Gaya" in IPAS learning, (3) describe the supporting and inhibiting factors of song-based audio media "Ragam Gaya" in IPAS learning, (4) describe the right solutions to overcome the inhibiting factors of song-based audio media "Ragam Gaya" in IPAS. Methodology: This study is qualitative with a descriptive design. Data collection involves in-depth interviews, observation, and documentation. The subjects of this study were principals, fourth-grade teachers, and fourth-grade students. Test data validity using data triangulation, including source and technical triangulation. Results: Based on the results of research that has been done, show that the application of song-based audio media "Ragam Gaya" in learning IPAS in material the influence of style on objects has a positive impact on fourth-grade students. The use of song-based audio media can foster students 'learning spirit, increase their interest in learning, and strengthen students' memory and understanding. Applications/Originality/Value: This research is important in improving students ' understanding and learning spirit towards learning IPAS materials about the influence of style on objects by using the song "Ragam Gaya".